Prevalence of urinary tract infection among children - Almofarreh, Moatez; Alowaa, Zainab; Junainah, Elaf; Alshahrani, Nourah; Alharbi, Meshal; Alkhalifah, Waleed; Aldmak, Amer; Salawi, Mohammed; Alaradi, Abdullah; Althomali, Ruya (International Journal of Contemporary Pediatrics, 2018)
Urinary tract infection is the third most common cause of febrile illness among children. UTI carries a considerable morbidity among this vulnerable age group because of its potential complications (e.g. hypertension and renal failure). Because diagnosis of UTI among the pediatric age group is challenging if solely based on clinical setting, knowledge of the actual prevalence rates of UTI among children is essential for pediatricians to determine the cost benefit effect of requesting investigations for suspected cases. Infants and children with UTI often present with fever with or without urinary symptoms. During assessment of a febrile child, pediatricians should be aware of the prevalence and risk factors for UTI in febrile children that necessitate further investigations. Prevalence of UTI among children is highly variable among different studies and the variability is attributed to multiple factors. This article aims at reviewing the prevalence of UTI in children reported among various literature studies and discussing factors influencing this prevalence.